Heavy metal contamination of Batanghari River, Jambi, Indonesia: determination based on sediment enrichment factor value - Badariah Badariah; Nisa Sukmawati; Sarah Fiebrina Heraningsih; Rainiyati Rainiyati; Ahmad Riduan; Riski Dwimalida Putri (Journal of Degraded and Mining Lands Management, 2023)
Batanghari River is the primary source of water for the people of Jambi. Batanghari River’s condition nowadays is worrying because its color is no longer clear. This research focused on determining the content of heavy metals in the Batanghari River's water and sediment. The conducted analysis is an ICP-MS analysis to determine the level of heavy metal (Cu, Cr, Co, Cd, Hg), and an enrichment factor calculation is conducted to determine the source of pollution. The enrichment factor value from the Batanghari River sediment sample declined with the following sequence Cd>Hg>Cu>Cr>Co, in 10 pinpoint locations. These indicate a high degree of anthropogenic activities along the Batanghari River which become the source of heavy metals entering the Batanghari River. The average concentration of heavy metals in the Batanghari River showed that the metal concentrations of Cd, Cu, and Hg are higher than the quality standards that have been set, whereas the metal concentrations of Cr and Co are still by the quality standards that have been set in PP 22 the year 2021.